Molecular Evidence of Chemical Disguise by the Socially Parasitic Spiny Ant Polyrhachis lamellidens (Hymenoptera: Formicidae) When Invading a Host Colony - Hironori Iwai; Hironori Iwai; Masaru Mori; Masaru Mori; Masaru Tomita; Masaru Tomita; Masaru Tomita; Nobuaki Kono; Nobuaki Kono; Kazuharu Arakawa; Kazuharu Arakawa; Kazuharu Arakawa (Frontiers in Ecology and Evolution, 2022)
While most ant species establish a colony independently, some socially parasitic ants build the foundation of their colony by invading other ant (host) colonies and utilizing their labor forces. Many socially parasitic ants disguise their cuticular hydrocarbon (CHC) profile, which is also known as signature mixture for nestmate discrimination, when invading the host colony. Since the strategy of chemical disguise is widespread in socially parasitic ants, elucidating the mechanism of chemical disguise will promote knowledge on the evolutionary history of social parasitism. However, detailed knowledge is still lacking, as the relevant information has only originated from circumstantial evidence, which was obtained from ecological observations. In this study, we investigated the mechanism of chemical disguise in a new queen of a temporary socially parasitic spiny ant (Polyrhachis lamellidens) by measuring its CHC profile, performing a tracing assay with labeled substances, and analyzing gene expression levels. First, after rubbing behavior was observed against the host workers, the CHC profile in P. lamellidens shifted to pronounced peaks that closely resembling that of the host workers. We also observed a reduction in aggressive behaviors by the host ant against P. lamellidens after rubbing behavior was performed. In addition, P. lamellidens acquired artificially-applied labeling substances from host workers through their rubbing behaviors, while gene expression profiling showed the expression of CHC synthesis-related genes did not change during this behavior. These results suggest that P. lamellidens directly obtains host CHCs through rubbing behavior, and these host CHCs enables P. lamellidens to remain disguised during colony invasion.